Sorting into payment schemes and medical treatment: A laboratory experiment - Brosig‐Koch, Jeannette; Kairies‐Schwarz, Nadja; Kokot, Johanna (Health economics, 2017)
In this study, we introduce the opportunity for physicians to sort into capitation or fee‐for‐service payment. Using a controlled medically framed laboratory experiment with a sequential within‐subject design allows isolating sorting from incentive effects. We observe a strong preference for fee‐for‐service payment, which does not depend on subjects' prior experience with one of the two payment schemes. Further, we identify a significant sorting effect. Subjects choosing capitation deviate ex ante less from patient‐optimal medical treatment than subjects who sort into fee‐for‐service payment. Particularly the latter become even less patient‐oriented after introducing the choice option. Consequently, the opportunity to choose between fee‐for‐service and capitation payment worsens patient treatment, if at all. Our results hold for medical and for nonmedical students.